Geographical patterns and environmental drivers of functional diversity and trait space of amphibians of Europe. Issue 1 (19th November 2019) - Tsianou, Mariana A.; Kallimanis, Athanasios S.
Abstract: Amphibians are among the most endangered group of vertebrates. To conserve their diversity we need to comprehend how functional diversity and species traits vary across environmental gradients. We investigate the distribution of functional diversity (functional richness–functional dispersion–functional evenness) and the environmental drivers (climate, energy availability, landscape and anthropogenic attributes) of these patterns for the 68 amphibian species of Europe using generalized least squares models and hierarchical partitioning. Based on eight functional traits, species were arranged in a multidimensional functional trait space and principal coordinates analysis (PCoA) was applied to investigate the occupancy of this space by amphibians. Functional richness mirrored species richness pattern and decreased towards higher latitudes; while, functional dispersion showed an even stronger negative correlation with latitude. Functional evenness did not display a clear latitudinal trend. Areas with higher functional richness and functional dispersion are associated with lower temperature seasonality and increased land cover diversity, in contrast areas with higher functional evenness are characterized by lower mean annual temperature. Climate seasonality mostly influenced the traits related to the first two PCoA axes (i.e., foraging location, mobility mode) which could have been considered as functional response traits and could be used as indicators to examine how communities respond to environmental change. Our work describes the macroecological patterns and discusses the relative importance of alternative underlying mechanisms driving functional diversity of this high‐risk taxonomical group and highlight that species richness presents only part of the biodiversity patterns, while other facets like functional evenness behave distinctively differently. Abstract : We investigate the distribution patterns of functional diversity (functional richness ‐ functional dispersion ‐ functional evenness) and the environmental drivers of these patterns for amphibians of Europe. The evidence presented here suggests that the distribution of amphibian functional diversity largely reflects species ‐ energy theory in terms of both the distribution of productive and ambient energy, habitat heterogeneity effects and filtering effects of harsh environmental conditions.